Elements of the crime of bankruptcy in Algerian law - KEHOUL, Oualid; ZOUAOUI, Elkahina (Journal of Human Sciences, 2024)
The offences of bankruptcy are extremely serious to trade, investment and the national economy, with negative and severe consequences in many areas, which have led countries to work against them. To address them, in order to strengthen confidence and credit among traders, and to create a secure and conducive economic environment for enterprises and national or foreign investors. The bankruptcy laws have therefore speedily enacted severe penalties for bankruptcy offenders, in order to deter those who think of their commission, limit their prevalence, foster the interests of all parties and protect trade and the economy in general.